7 Correlation of aortic valve annular plane assessment by pre-procedural computed tomography versus on-table 3-dimensional rotational angiography. (October 2018) - Murphy, S; Malone, C; Tanner, R; Blake, G; Sugrue, D; Byrne, R; McGorrigan, C; Barton, D; Margey, R; Casserly, I
Abstract : Background: Accurate assessment of the aortic valve annular plane (AVAP) is critical during transcatheter aortic valve Implantation (TAVI) procedures, particularly for placement of balloon-expandable TAVI valves. Pre-procedural computed tomography (CT) angiography has typically been used to determine the AVAP. However, this may differ from the in-lab AVAP determined during the TAVI procedure due to differences in patient position between the two assessments or compromised quality of the CT dataset. The aim of this study was to assess the correlation between the AVAP obtained by pre-procedural CT angiography with in-lab AVAP assessment using 3-dimensional rotational angiography (3DRA). Methods: Using a prospective TAVI database, patients undergoing trans-femoral TAVI who had had both pre-procedural CT angiography and on-table 3DRA were identified. The AVAP assessment by CT angiography was performed using 3Mensio software (Pie Medical Imaging). 3DRA assessment was performed using DynaCT (Siemens). Correlation was reported according to the concordance correlation coefficient (ρc). Results: From a total of 113 patients undergoing TAVI between June 2014 and August 2017 in the Mater Private Hospital, 100 patients were eligible for inclusion in the analysis. The mean AVAP as assessed by CT angiography was LAO 8.6°±10.5° and caudal 1.8°±10.7°. The mean AVAP as assessed by 3DRA was LAO 9.9°±9.2° and caudal 5.11°±8.7° (figure 1). The concordance correlation coefficients for the LAO/RAO and cranial/caudal planes of the AVAP were 0.52 (95% CI: 0.38 to 0.66) and 0.56 (95% CI 0.43 to 0.68), respectively. The proportion of patients in whom there was a≥5° and ≥10° discrepancy between the CT and 3DRA assessments of the AVAP for the LAO/RAO, the cranial/caudal, and both LAO/RAO and cranial/caudal planes is shown in figure 2. Conclusions: In this large consecutive patient series, correlation between pre-procedural CT and on-table 3DRA in the prediction of the AVAP was moderate. In approximately one-quarter of patients, there was a≥10° discrepancy in either the LAO/RAO or cranial/caudal plane, while in 10% of patients there was a≥10° discrepancy in both planes. These data support the value of an in-lab assessment of the AVAP to optimize clinical outcomes during TAVI procedures.